Application of Herbal Traditional Chinese Medicine in the Treatment of Acute Kidney Injury - Hai-Di Li; Hai-Di Li; Hai-Di Li; Hai-Di Li; Xiao-Ming Meng; Xiao-Ming Meng; Xiao-Ming Meng; Xiao-Ming Meng; Cheng Huang; Cheng Huang; Cheng Huang; Cheng Huang; et al. (Frontiers Media S.A., 2019)
Acute kidney injury (AKI) is a clinical syndrome characterized by a rapid loss of renal function, which may further develop into chronic kidney damage (CKD) or even end-stage renal disease (ESRD). AKI is a global health problem associated with high morbidity and costly treatments, and there is no specific or effective strategy to treat AKI. In recent years, Traditional Chinese Medicine (TCM) has attracted more attention, with lines of evidence showing that application of TCM improved AKI, and the mechanisms of action for some TCMs have been well illustrated. However, reviews summarizing the progress in this field are still lacking. In this paper, we reviewed TCM preparations and TCM monomers in the treatment of AKI over the last 10 years, describing their renal protective effects and mechanisms of action, including alleviating inflammation, programmed cell death, necrosis, and reactive oxygen species. By focusing on the mechanisms of TCMs to improve renal function, we provide effective complementary evidence to promote the development of TCMs to treat AKI. Moreover, we also summarized TCMs with nephrotoxicity, which provides a more comprehensive understanding of TCMs in the treatment of AKI. This review may provide a theoretical basis for the clinical application of TCMs in the future.